2020
DOI: 10.1039/d0ra05513a
|View full text |Cite
|
Sign up to set email alerts
|

A nanocomposite paper comprising calcium silicate hydrate nanosheets and cellulose nanofibers for high-performance water purification

Abstract: A nanocomposite paper with high water permeability and removal efficiency was prepared for the removal of organic and inorganic contaminants by filtration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Treatments to modify cellulose fibers are used to optimize an improvement in the interface between fibers and cementitious systems [29], Biswas et al [30] modified the surface of the cellulose fiber with calcium silicate and found that there are large amounts of Ca and Si bonds in the cellulosic hydroxyls. Demonstrating affinity between the molecules, Li et al [31] produced nanocomposites based on calcium silicate and nanofibrillated cellulose and verified high interaction with the cementitious matrix.…”
Section: Cellulose Fiber (Fc)mentioning
confidence: 99%
“…Treatments to modify cellulose fibers are used to optimize an improvement in the interface between fibers and cementitious systems [29], Biswas et al [30] modified the surface of the cellulose fiber with calcium silicate and found that there are large amounts of Ca and Si bonds in the cellulosic hydroxyls. Demonstrating affinity between the molecules, Li et al [31] produced nanocomposites based on calcium silicate and nanofibrillated cellulose and verified high interaction with the cementitious matrix.…”
Section: Cellulose Fiber (Fc)mentioning
confidence: 99%
“…Therefore, uid pressure loss is generally accompanied by inertia loss, resulting in a nonlinear increase in the pressure drop. Forchheimer modied Darcy's law and presented the empirical relationship of uid ow resistance through porous media, 25,26 as shown in eqn (3).…”
Section: Pore Size Distribution Xrd and Air Permeability Testmentioning
confidence: 99%
“…Porous materials are characterized by a light weight and large specic surface area due to a large number of pore structures inside them 1,2 and are widely used in ltration, 3,4 energy storage, 5,6 heat dissipation 7 and other elds. With the further development of their application eld, the demands on the properties of porous materials are increasing.…”
Section: Introductionmentioning
confidence: 99%